The Influence of Job Rotation and Job Operational Standards on Employee Achievement - Roza Noverita; Afni Yeni; Wahyu Indah Mursalini (ProBisnis : Jurnal Manajemen, 2023)
This research aims to determine the effect of work rotation and work operational standards on the work performance of BKPSDM employees in Solok Regency with a sample of 38 respondents who were studied using quantitative methods. Based on the results of statistical analysis, it can be interpreted that Job Rotation partially has a significant effect on Employee Work Performance, this is proven by the t test with a significant value of tcount 5.360 > ttable 2.030 in the significance level value, 0.000 < 0.0. So it can be interpreted that job rotation has a significant effect on employee work performance. Based on the results of statistical analysis, it can be concluded that Work Operational Standards partially have a significant effect on the Work Performance of Solok Regency BKPSDM Employees. This is proven by the T test with a significant value of tcount 2.691 > t table 2.030 and a significance level value of 0.011 < 0.05. So it can be concluded that Work Operational Standards have a significant effect on the Work Performance of Solok Regency BKPSDM Employees. Simultaneously, Job Rotation and Work Operational Standards have a significant effect on the Job Performance of Solok Regency BKPSDM Employees. This is proven by using the F test with a significant value of fcount 21.159 > ftable 3.27 and the resulting significant value is 0.000 and this value is much smaller than a (0.05). This can also be seen from the R Square value obtained at 0.547 or 54.7% and the remaining 45.3% is influenced by other variables not included in this research. Keywords: Job Rotation, Work Operational Standards, and Work Performance